Seroprevalence of antibodies to tick-borne encephalitis virus and Anaplasma phagocytophilum in healthy adults from western Norway. Issue 1 (January 2015) - Hjetland, Reidar; Henningsson, Anna J.; Vainio, Kirsti; Dudman, Susanne G.; Grude, Nils; Ulvestad, Elling
Abstract: The aim of this study was to assess the seroprevalence of antibodies to tick-borne encephalitis virus (TBEV) and Anaplasma phagocytophilum in a healthy adult population from Sogn and Fjordane county in western Norway. Sera from 1, 213 blood donors were analysed for IgG-antibodies to TBEV, and a random subgroup of 301 donors for IgG to A. phagocytophilum. In the TBEV ELISA, five (0.4%) sera were positive. These were all interpreted as "false" positives, as four had received vaccines against flaviviruses, and the remaining was negative for neutralizing antibodies to TBEV. Antibodies to A. phagocytophilum were detected by indirect immunofluorescence in 49 (16.2%) subjects (titer range 80-1280). The results indicate that TBE currently is not endemic in this part of western Norway. However, there is serological evidence of the existence of human granulocytic anaplasmosis in the population.